Tourism Object Development Strategy in Rejang Lebong Regency Bengkulu Province - Rani Kurniawati; Ninuk Triyanti; Dahyar Daraba (PINISI Discretion Review, 2019)
The sector developed in Indonesia at this time is the tourism sector. The purpose of this study is to find out how the development of attractions, supporting and inhibiting factors, and formulate strategies in the development of tourism objects in Rejang Lebong Regency. This research uses descriptive research method with a qualitative approach. Data in this study were collected through interviews, documentation, observation and data triangulation. The analysis technique used in writing uses the SWOT analysis and Litmust Test to be reduced, presented and concluded. The results of research strategies for developing tourism objects in Rejang Lebong Regency are still not maximal, because there are many weaknesses in each component in the tourism area which become a benchmark for the development of Bengkulu Province tourist destinations, Rejang Lebong. The influencing factors are internal factors, namely strengths and weaknesses and external factors, namely opportunities and threats. Based on these factors, researchers can reformulate the strategy in the development of attractions in Rejang Lebong Regency, Bengkulu Province